IMPLEMENTASI CUTI BERSYARAT SEBAGAI WUJUD PEMBINAAN BAGI NARAPIDANADI RUMAH TAHANAN NEGARA KELAS IIA YOGYAKARTA - A. Vinda Paramitasari; Ishviati Joenaini Koenti; Sigit Setyadi (Universitas Janabadra, 2018)
The imprisonment system initially emphasizes elements of revenge and enmity. But now the system of imprisonment is seen no longer in line with the concept of rehabilitation and social reintegration that aims to make inmates acceptable again by the community and no longer repeat the mistakes he made. One of the stages of coaching that every prisoner must take is the stage of social reintegration. Every prisoner who is in Rumah Tahanan Negara Kelas IIA Yogyakarta must follow in an orderly manner every specific guidance and activity program conducted by Rumah Tahanan Negara Kelas IIA Yogyakarta. If in the coaching program runs well, then the inmates who follow the program are entitled to an appreciation, one of which is the provision of Conditional Leave.The results obtained in this study are the mechanism of the release of conditional leave declaration and the implementation of conditional leave in Rumah Tahanan Negara Kelas IIA Yogyakarta.